2013
DOI: 10.1007/s12594-013-0089-4
|View full text |Cite
|
Sign up to set email alerts
|

Clay Mineralogy of the Pleistocene Soil Horizon in Barind Tract, Bangladesh

Abstract: Pleistocene red soil horizons were exposed in different areas of the Barind Tract in north-west Bangladesh. X-ray diffractions of twenty seven samples from different depths of these soil horizons revealed that the soil horizons consisted of kaolinite, illite and chrysotile with significant amount of opal-CT. Samples from Maddhapara, Bogra, and Nachole contain kaolinite, illite, quartz and opal-CT, and the samples from Kantabari contain chrysotile instead of kaolinite. Clay mineral compositions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, other soil horizons of illite-kaolinite clay mineral assemblage indicate that soils were possibly formed under humid, temperate and well drained conditions. These two soil horizons were formed under different geochemical, geomorphological and climatic conditions from different parent materials (Aftabuzzaman et al 2013). This opal-CT along with the general lack of fossils and presence of glass shards was indicative of a volcanogenic rather than biogenic origin for the Opal-CT in the Barind tract.…”
Section: Thick Top Clay Layermentioning
confidence: 89%
See 1 more Smart Citation
“…However, other soil horizons of illite-kaolinite clay mineral assemblage indicate that soils were possibly formed under humid, temperate and well drained conditions. These two soil horizons were formed under different geochemical, geomorphological and climatic conditions from different parent materials (Aftabuzzaman et al 2013). This opal-CT along with the general lack of fossils and presence of glass shards was indicative of a volcanogenic rather than biogenic origin for the Opal-CT in the Barind tract.…”
Section: Thick Top Clay Layermentioning
confidence: 89%
“…Barind Tract in north-west Bangladesh geomorphologically formed with Pleistocene red soil. Aftabuzzaman et al (2013) carried out detailed investigation on the formation of Barind tract and found that Barind tract consisted of kaolinite, illite and chrysotile with significant amount of opal-CT. The soil sample collected from Nachole and examined by X-ray diffractions showed the composition of kaolinite, illite, quartz and opal-CT while in places it was found chrysotile instead of kaolinite.…”
Section: Thick Top Clay Layermentioning
confidence: 99%
“…The average clay content of this facies is ~71%, and clay mineralogy is a suite of inherited minerals that includes chlorite, illite, kaolinite, and smectite phases, with no dominant mineral trends (Fig. a); this mixed composition is similar to clay mineral distributions found in Holocene fluvial overbank deposits throughout the delta (Heroy et al ., ; Tennant, ; Aftabuzzaman et al ., ). Under magnification, these silts display a uniformly euhedral mineral habit with relatively large crystals (up to ~50 μm) (Fig.…”
Section: Paleosols Clay Mineralogy and Microtextural Morphology Of mentioning
confidence: 97%
“…2. Upper units consisted of Cenozoic age sediments with the youngest being the Pleistocene Barind clay unit comprising red soils dominated by clay minerals including kaolinite, illite and chrysotile (Aftabuzzaman et al 2013).…”
Section: Samplingmentioning
confidence: 99%